2019
DOI: 10.2319/071718-520.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of BALP, CTX-I, and IL-4 levels around miniscrew implants during orthodontic tooth movement between two different amounts of force

Abstract: Objectives: To evaluate the Interleukin-4 (IL-4), bone-specific alkaline phosphatase (BALP), and C-telopeptide of type I collagen (CTX-I) levels in peri-miniscrew crevicular fluid (PMCF) during orthodontic tooth movement between 75 and 150 g of distalization force. Materials and Methods: Thirty miniscrews were placed bilaterally between the maxillary second premolars and first molars. The right and the left maxillary canines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…As IL‐4 is known to affect bone metabolism and cause bone remodelling, exogenous IL‐4 was administered at the relapsing stage. However, there is not yet enough evidence to confirm that endogenous IL‐4 affects bone formation during orthodontic treatment (Cesur et al., 2019; Gross et al., 2017; He et al., 2015; Wehrhan et al., 2019; Yashin et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As IL‐4 is known to affect bone metabolism and cause bone remodelling, exogenous IL‐4 was administered at the relapsing stage. However, there is not yet enough evidence to confirm that endogenous IL‐4 affects bone formation during orthodontic treatment (Cesur et al., 2019; Gross et al., 2017; He et al., 2015; Wehrhan et al., 2019; Yashin et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A high‐speed dental handpiece (NSK Ltd) with a needle was used to grind a 0.5–1 mm deep retention groove on the labial and the distal surfaces of the maxillary incisors and on the mesial axial angle of the maxillary first molars. Then, a 0.25 mm orthodontic ligation wire (Shinye) was applied to ligate a nickel–titanium tension spring (length: 6 mm, diameter: 0.3 mm) (Shinye) between the maxillary incisor and the first molar with a force of 50 g (Cesur et al., 2019; Iwasaki et al., 2000). The bilateral maxillary incisors were made to act as anchorages to pull the first molars mesially.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 However, evidences have not reached a consensus regarding the exact magnitude of the OOF and it is urgent to explore how to evaluate it in clinical practice. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%
“…There was a study (8,9) found that miniscrews on the side of the mouth loaded with lighter forces were substantially more stable than those loaded with larger forces. In another investigation, miniscrews loaded with 100 or 200 g had much greater success rates than unloaded miniscrews and those loaded with 50 g (10) .…”
Section: Introductionmentioning
confidence: 99%